Sexual violence against women and girls as a weapon of war and genocide Yezidi women and girls, for example - امین, م. رۆشنا جمال محمود امین (Sulaimani Journal for Humanities, 2024)
This paper entitled (Sexual Violence against Women and Girls as a Weapon of War and Genocide. Yazidi Women and Girls as an Example), presents the concept of sexual violence and its use as a weapon in war, armed conflict and genocide against women and girls A secondary effect of war and genocides would be detected. This topic has been the focus of public and academic attention, especially in recent years. According to academic research, sexual violence is often used as a weapon of war to impose power on the community of the victim group, through the rape, humiliation, intimidation and oppression of their wives and daughters by armed groups, militias, government forces and even civilians. Today, this violence is practiced in many countries around the world, such as Ukraine, Syria, Afghanistan, Iraq, Ethiopia and others. This study investigates the causes of sexual violence in wars and genocides and the mechanisms of preventing and protecting target groups, especially women and girls from this heinous crime. The study also attempts to discuss the most obvious effects of this crime against humanity It puts the religious. This paper focuses on the use of sexual violence as a weapon against Kurdish women and girls, especially Yazidi Kurdish women and girls, during the genocide of Sinjar and surrounding areas by the terrorists of the Islamic State of Iraq and Syria (ISIS) in In addition, the study presents the most important international efforts that have been taken to legally combat this crime in order to prohibit and punish the crime of sexual violence and ensure the rights of victims.
Keywords: Sexual Violence; War; Genocide of Yezidi Women and Girls; ISIS